ENSURING THE UNIFORMITY OF COURT PRACTICE THROUGH THE PRISM OF THE CONCEPT OF “LIVING LAW” BY EUGEN ERHLICH - SAVCHYN, NELYA (Ehrlich's Journal, 2023)
The article analyzes the legal literature on the understanding and meaning of the concept of “Living Law” by E. Ehrlich. Various works of the scientist on his own understanding of “Living Law” are studied. The concept of “Living Law”, like the doctrine of natural law, has a direct impact on the construction of human legal consciousness, the formation of civil society and the rule of law. The basic tenets of the concept of “Living Law” indicate that the law must keep pace with the times and change in accordance with the new challenges of society. It is noted what is the impact of positive and natural law on social relations, which are always developing. The concept and meaning of judicial practice are revealed. The unity of judicial practice is a guarantee of public confidence in the judiciary. The influence of Ehrlich’s concept of “Living Law” on ensuring the unity of judicial practice is revealed. The analysis of the legal literature on the study of the legal nature of the judicial decisions of the supreme courts, namely the Supreme Court, has been conducted. It has been proven that the Supreme Court has a special legal status, which is determined by the fact that it not only administers justice, but is also called to perform the function of ensuring equal application of the law by all courts. The main purpose of the highest judicial body of the state is not only to administer justice, but also to ensure equal interpretation and application of the law by all courts. It is necessary that the laws be applied equally in similar cases and in similar factual circumstances, which in turn will guarantee the stability of legal relations and confidence in the legitimacy of future behavior. Based on the study, the advantages of ensuring the unity of judicial practice are emphasized.